How to motivate employees - Finney, Martha I. (FT Press Delivers elements., 2011)
This Element is an excerpt from The Truth About Getting the Best from People (9780137080571) by Martha I. Finney. Available in print and digital formats. If you're a manager, you're a career coach! Do it right, and motivate employees in practically any environment. No one is in a dead-end job, even those who think they are. There's always a way out-or up-from any job. Help employees find the line of sight between what they do now and what they'd someday like to do. By helping employees control their career prospects, managers gain more control over their own prospects...